Misteri Rumah yang Ganjil dalam Novel Teka-Teki Rumah Aneh: Psikologi Forensik - Puspita*, Siti Fauziah Ayu; Ahmadi, Anas (Universitas Suryakanca, 2025)
This article will describe the results of the study of the novel